What Active Learning and Authentic Assessment in Higher Education Can Do for the World - Salinas-Navarro, David Ernesto; Vilalta-Perdomo, Eliseo (Emerald Publishing Limited, 2025)
This chapter examines how active learning and authentic assessment can impact learners, society and the world. It advocates for extending traditional classroom pedagogies to real-world experiences, where students can become knowledge producers and problem solvers. In today's higher education, it is essential to equip students with skills to address contemporary challenges. Active learning fosters reflective and practical growth, while authentic assessment encourages engagement with realistic issues, self-directed learning and critical thinking. By placing students in real-world scenarios, these approaches enhance their learning outcome development and foster meaningful contributions to communities and society. This is a shift in learning from classroom spaces to real-world environments. Accordingly, this type of learning supports novel productive interactions for societal impact and community support beyond traditional academic mechanisms. This chapter discusses these concepts in light of the ideas presented in this book in previous sections. Overall, the different uses and applications of active learning for authentic assessment illustrate the link of active pedagogies with realistic learning scenarios and the production of a positive impact on learners and society. Future work could explore the long-term possibilities of these approaches on society and communities, investigating how these could be adapted across disciplines or scaled to larger educational contexts. ©The authors ©Emerald Publishing Limited.
Keywords: Community engagement; Educational innovation; Higher education; Learning experiences; Learning scenarios; Societal impact